Pemanfaatan Media Sosial Instagram Terhadap Minat Beli Konsumen Pada Raysa Fashion - Yoeliastuti, Yoeliastuti; Nurlina, Nurlina (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2022)
The research aims to determine the extent to which the use of Instagram media in attracting consumer buying interest in Raysa Fashion. This type of research uses quantitative data by measuring numbers. The analysis technique used is descriptive by testing simple linear regression analysis. The data collection method was carried out by interviewing techniques and distributing questionnaires to customers who took part in Instragram Raysa Fashion with a sample of 50 customers who filled out a questionnaire. The test results show that the tested data is declared valid and reliable. Utilization of Instagram media also shows a positive and significant influence on purchase intention